NESTING BEHAVIORAL ADAPTATIONS OF ORANGUTAN (PONGO PYGMAEUS MORIO) IN COAL MINING AREA IN EAST KALIMANTAN - Liza Niningsih; Sri Suci Utami Atmoko; Hadi S Alikodra; Yeni A Mulyani (Forestry Study Program University Of Mataram, 2021)
Coal mining changed forest structure and composition, it caused large negative impacts on the orangutan. In order to mitigate those negative effects, it is crucial to understand their nesting behavior adaptation in mining area. We investigated 74 times nested event in coal mining rehabilition area (CMRA) in East Kutai and 123 times in the Kutai National Park (Prevab) from October 2013 to September 2014 and include only night nests. We compared both habitats. Orangutans in CMRA built the nest later than in Prevab and used 15 species of trees as nests sites intensively on Senna siamea and Gmelina arborea. In Prevab, 35 species with the higher frequencies on Eusideroxylon zwageri and Dracontomelon dao. The average diameter of nest trees in CMRA smaller than Prevab. The height of nest trees in CMRA with the highest frequency was in 10.1-15 m, while in Prevab was as in 20.1-25 m. Orangutans in CMRA nested at the height of <15 m, lower than in Prevab was >20 m. Reused nest in CMRA was higher than in Prevab. Orangutans in CMRA more often built nests at the peak and limb, while in Prevab at the limb and peak. Orangutans in CMRA had learned to utilize various species and dimensions of trees as the place to build nests.